2008
DOI: 10.1007/s10499-008-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimum ration level for better growth, conversion efficiencies and body composition of fingerling Heteropneustes fossilis (Bloch)

Abstract: The effects of ration levels on growth, conversion efficiencies and body composition of fingerling Heteropneustes fossilis (6.8 ± 0.04 cm, 5.0 ± 0.02 g) were studied by feeding isonitrogenous (40% crude protein) and isocaloric (19.06 MJ kg -1 gross energy) diets representing 1, 3, 5, 7 and 9% of the body weight (BW) day -1 to triplicate groups of fish . Growth performance of the fish fed at the various ration levels was evaluated on the basis of live weight gain percentage (LWG%), feed conversion ratio (FCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…Previous studies have reported two main types of growth-ration relationships: a simple linear regression (Niimi and Beamish, 1974;Cui et al, 1996; and, more commonly, an increasing but decelerating curve (Jobling, 1994;Han et al, 2004;Khan and Abidi, 2010). In the present study, the growth-ration relationship over the whole ration range was represented by a decelerating curve and the conversion effi ciency was highest at an intermediate ration level.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Previous studies have reported two main types of growth-ration relationships: a simple linear regression (Niimi and Beamish, 1974;Cui et al, 1996; and, more commonly, an increasing but decelerating curve (Jobling, 1994;Han et al, 2004;Khan and Abidi, 2010). In the present study, the growth-ration relationship over the whole ration range was represented by a decelerating curve and the conversion effi ciency was highest at an intermediate ration level.…”
Section: Discussionsupporting
confidence: 50%
“…A typical growthration relationship for fi sh is represented by a decelerating curve (Brett and Groves, 1979;Han et al, 2004;Khan and Abidi, 2010), but studies have also shown that linear relationships are common (Sullivan, 1982;Cui et al, 1996;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross feed conversion efficiency (GFCE) over the entire experiment was calculated for each ration as the change in WW divided by total dry weight of feed delivered to the tank (Stickney, 2005). Since GFCE increases with ration to a point, then decreases as ration exceeds maximum intake, a second order polynomial (quadratic function) was used to model the relationship between GFCE and ration (Zeitoun et al, 1976;Khan and Abidi, 2010). Survival was high for most rations, but decreased linearly with decreasing ration when levels became limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on some aspects of nutritional requirements of this fish are available (Niamat and Jafri 1984; Akand et al 1991; Anwar and Jafri 1992; Firdaus 1993; Firdaus et al 1994; Firdaus and Jafri 1996; Mohamed 2001; Mohamed and Ibrahim 2001; Firdaus et al 2002; Usmani et al 2003; Khan and Abidi 2009; Siddiqui and Khan 2009; Khan and Abidi 2011a, 2011b), no information is available on its optimum P/E ratio in diets for H. fossilis . This study was, therefore, conducted with a view to optimize dietary P/E ratio so that protein and energy balanced, cost‐effective, practical diet could be formulated for the intensive culture of H. fossilis .…”
mentioning
confidence: 99%